Enantioseparation Of Ketoconazole And Miconazole By Capillary Electrophoresis Using Hydroxypropyl-Β-Cyclodextrin As A Chiral Selector - Azhari, Nurul Raihana (2019)
Capillary electrophoresis (CE) method employing native β-cyclodextrin (β-CD) and modified hydroxypropyl-β-cyclodextrin (HP-β-CD) as chiral selectors was studied and compared for simultaneous enantioseparation of two imidazole antifungal agents. The two imidazole antifungals agents which were ketoconazole and miconazole were successfully resolved with good resolution (Rs: 1.6 and 3.7, respectively) within 16 min using 1.5 mM of HP-β-CD in the background electrolyte (BGE) containing 35 mM of tris-phosphate buffer (pH 2.5) at the 25 ºC and 25 kV. The samples were injected hydrodynamically at 50 mbar for 5 sec and detection was carried out at 200 nm. The method of each enantiomer was linear over the the concentration ranges of 0.25 – 50 mg L-1 with high coefficient of determination (R2 > 0.999) and the limit of determination (LOD) and limit of quantification (LOQ) were 0.075 and 0.250 mg L-1, respectively. The proposed method was also applied to selected antifungal cream samples and good recoveries were found, ranging from 82.0 – 105.7%, (RSD < 7%, n = 3). In addition, in order to understand in depth the possible chiral separation mechanism of both imidazole compounds with β-CD and HP-β-CD, the formation of inclusion complexes were analyzed using 1H NMR spectroscopy and UV-Vis spectrophotometry techniques and lastly, proposed structure of inclusion complexes were drawn and presented.